THE INFLUENCE OF PROBLEM- BASED LEARNING MODELS AND SELF-CONCEPT ON HIGHER ORDER THINKING ABILITIES (HOTS) - Zulvia Misykah; Putri Sari Ulfa Sembiring; Dewi Sartika Panggabean; Fira Yunia (Sean Institute, 2023)
This study aims to determine (1) the influence of PBL strategy on higher order thinking skills, (2) the influence of on Highe rOrder Thinking Ability, (3) to see the interaction between learning strategies and intellectual intelligence, this type of research is experimental research with design Experimental research design. The sample in this study is the IVc class as the experimental class and IVd class as the control class in Parmiyatu Wassa’adah Tembung. Data collection method is done by test, the initial test is done to classify the level of Self Concept, in this case, is done using the Quetionnaire test, then the results are divided into two levels, namely self concept high and self concept on average, always given action with the PBL model and strategy expository. Post tests are given to measure high-level thinking skills, with Mathematics questions designed by researchers following Olympic and TIMSS questions, which are then expertly Expected. The results of the high-level thinking skills test are then analyzed by prerequisite tests which include, normality test, homogeneity test, and Anava test. Based on the results of data analysis obtained a significant influence on the application of the PBL model to higher-order thinking skills than the expository strategy of fourth grade students of Parmiyatu Wassa’adah Elementary School, there is a significant influence on high self concept on higher-order thinking skills than average self concept average fourth grade students of Parmiyatu Wassa’adah Elementary School, then there is interaction between learning strategies and self concept on high-level thinking skills of class IV students of Parmiyatu Wassa’adah Elementary School.